CdZnSe@ZnSe colloidal alloy quantum dots for high-efficiency all-inorganic perovskite solar cells. Issue 69 (7th August 2018) - Li, Qinghua; Bai, Jinke; Zhang, Tingting; Nie, Chao; Duan, Jialong; Tang, Qunwei
Abstract : We present here the successful fabrication of core–shell constructed CdZnSe@ZnSe colloidal alloy quantum dots with tunable optical properties using a hot-injection method, demonstrating great potential in photovoltaic devices. Abstract : We present here the successful fabrication of core–shell constructed CdZnSe@ZnSe colloidal alloy quantum dots with tunable optical properties using a hot-injection method, demonstrating great potential in photovoltaic devices. Upon employment as charge extraction materials in all-inorganic perovskite solar cells, an enhanced power conversion efficiency up to 8.65% has been achieved arising from the boosted charge transfer dynamics.